Risk Assessment of Chlorothalonil as a Probable Human Carcinogen on Selected Vegetables in an Eastern China Province - Sun, Chen-Xi; Liu, Bing; Wang, Wen-Bo; Yuan, Xue-Xia; Wu, Yuan-Juan (Frontiers in Public Health, 2022)
Objectives This study aimed to provide an assessment of chlorothalonil's possible carcinogenic risk posed to the public. In combination and comparison with the non-carcinogenic risk, the results hopefully could provide useful insights, early warning, and references for policy formulation. Methods This study firstly investigated the occurrence of chlorothalonil on selected key vegetables for different scenarios, and then conducted an exposure assessment with officially published data. Lastly, both the non-carcinogenic and carcinogenic risk of chlorothalonil were calculated by using Monte-Carlo simulation. Results Even though mean non-carcinogenic risks of chlorothalonil for all scenarios were below threshold value, the mean carcinogenic risks for maximum-risk scenario and most-likely risk scenario were mostly above threshold value. High probabilities of exceedance of threshold value existed for carcinogenic risk under all scenarios. Conclusion Potential threat to public health existed for conventionally ‘safe' pesticide if considering the possible carcinogenicity. Extra caution should be taken and the potential carcinogenic effects should be included into consideration for better protection of public health during the policy formulation process.